FACTORS AFFACTING THE CAPITAL MOBILIZATION OUTCOME OF THE NATIONAL NEW RURAL DEVELOPMENT PROGRAM IN THE NORTHERN MIDLANDS AND MOUNTAINOUS REGIONS - Van Tuan, Nguyen; Thi Han, Doan (Journal of Forestry Science and Technology, 2016)
Effective capital mobilization is the most challenge task in the National New Rural Development Program (NNRD) in practice. So far, the capital for this program has mainly been mobilized from the local government, and the local community. This study has been conducted based on the structured survey of 345 people in 3 provinces Son La, Phu Tho, and Lang Son. The EFA (Exploratory Factor Analysis) method has been applied to quantify the main factors affecting the capital mobilization outcome in these provinces.